2017
DOI: 10.5530/jyp.2017.9.113
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy Induced Adverse Drug Reactions in Cancer Patients in a Tertiary Care Hospital in South India

Abstract: Objective: To evaluate the pattern of adverse drug reactions (ADRs) reported in cancer patients receiving anticancer drugs in an adverse drug reaction monitoring centre (AMC). Methods: The anticancer drug related ADRs received in AMC through spontaneous reporting and active surveillance methods from January 2014 to June 2016 were analyzed for demographic profile, organ system and department wise distribution of ADRs, common ADRs encountered, drugs responsible for causing ADRs, ADRs reported by healthcare profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
(6 reference statements)
1
7
1
Order By: Relevance
“…Our finding is similar to the study carried out by Sharma et al [5] that showed adverse effects in the 41-60 years age group. This finding is also similar to the report of Pai et al [6] who also reported average age of subjects 55.98 years and 52.96 years in men and women respectively and likewise, a study of Behera et al [7] which showed adverse reactions in 41-60 years age group was highest. This can be because of the high occurrence of cancers in this particular age group.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding is similar to the study carried out by Sharma et al [5] that showed adverse effects in the 41-60 years age group. This finding is also similar to the report of Pai et al [6] who also reported average age of subjects 55.98 years and 52.96 years in men and women respectively and likewise, a study of Behera et al [7] which showed adverse reactions in 41-60 years age group was highest. This can be because of the high occurrence of cancers in this particular age group.…”
Section: Discussionsupporting
confidence: 91%
“…In general, the main goal of breast cancer chemotherapy is to increase disease-free survival and overall survival of the patients [1,2] though it causes diverse aspects of adverse drug reactions [3,4] that will deteriorate different domains of the patients' quality of life [19]. On the contrary, receiving less than optimum RDI (i.e., RDI < 85%) resulted in lower survival for those patients [29,31,47,55].…”
Section: Discussionmentioning
confidence: 99%
“…Behera et al 8 conducted a study in a tertiary care hospital in India, claiming that 21.8% of ADRs were due to antineoplastic agents. However, in present research work, patients were observed with significant doubtful, probable, and possible ADRs.…”
Section: Discussionmentioning
confidence: 99%